Redescription of Eidophasia tauricella Staudinger, 1880 (Lepidoptera, Plutellidae) with first description of the female genitalia - Baraniak, Edward; Walczak, Urszula (Zootaxa, 2015)
Eidophasia tauricella Staudinger, 1880 is redescribed with a photo of the type specimen. The female genitalia are described for the first time.